APPLICATION OF A COMPLEX APPROACH IN FORMING A POSITIVE BRAND IMAGE - Kniazieva, Tetiana; Lisova, Karina (Socio-economic relations in the digital society, 2023)
This article analyzes the application of the holistic marketing system in building a positive brand image. The relevance of writing a paper is determined by changes in the market that create new rules for conducting business. The main opinions of scientists regarding the concept of image and its types, the application of the concept of holistic marketing and its components are considered. In addition, the technology of building a positive brand image was described, which consists of six points (identification of the target audience, its needs, formation of a value proposition and identifying features for it, planning a marketing campaign and further consistency in one's actions). In addition, it is determined that the intersection of the components of holistic marketing forms a proper image. The application of the components of the concept of holistic marketing (relationship marketing, socio-ethical marketing, integrated marketing and internal marketing) on the example of Ukrainian enterprises in the dairy industry is considered in detail. Having determined all the theoretical aspects, the transition to the research object took place, namely TM "Dooobra Ferma". In the article, the authors studied basic information about the brand, internal and external components of activities that directly affect its development. It was determined that TM "Dooobra Ferma" skillfully applies the components of the holistic marketing system to strengthen its competitiveness and build a positive brand.
Keywords: brand image; integrated approaches; holistic marketing; brand image building